Consumer acceptance of protein beverage ingredients: Less is more - D. Rovai; M.E. Watson; D.M. Barbano; M.A. Drake (Journal of Dairy Science)
ABSTRACT: An array of ingredients is added to protein beverage formulations. These ingredients may not be desirable to consumers. Our objective was to determine consumer perception of ingredients in protein beverages. An online survey was conducted with protein beverage consumers (n = 405). Maximum difference scaling and projective mapping were applied to determine the relative acceptance of ingredients based on their functional role (protein source, sweetener, stabilizer, thickener). Subsequently, 4 120-min focus groups were conducted (n = 25 consumers). Survey data were evaluated by univariate and multivariate statistics. Consumer sentiment from focus groups was compiled and grouped based on themes that emerged across multiple focus groups. Consumers placed the highest importance on the amount of protein followed by protein type in protein beverages. Plant protein, whey protein, and milk protein were most appealing, whereas soy protein, collagen, and casein or caseinates were less appealing. Natural sweeteners (agave, monk fruit, cane sugar) were the most appealing sweeteners. Fibers and starches were more appealing than gums (carrageenan, gellan gum). Stabilizers were the least desirable class of beverage ingredients, with sodium and potassium phosphates the least desirable. In regard to the package of a protein beverage, consumers placed the greatest importance on recognizable ingredients and plain language. Consistent with survey results, consumers in focus groups expressed skepticism and feeling overwhelmed by all of the ingredients on the label of protein beverages. Protein was their primary desire and the presence of sweeteners was acceptable, but they did not desire additional ingredients. There is an opportunity to increase the acceptance and competitiveness of dairy protein beverages by reformulating beverages to include fewer and more familiar ingredients. Functional proteins, such as those derived from dairy, may have opportunities to exclude undesirable ingredients (stabilizers, thickeners) from the label.